LANDASAN ETIKA DALAM EKONOMI ISLAM - Rina Desiana; Noni Afrianty (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
Every economic system is certainly based on the ideology that provides the  foundation and goal on the one hand and the axioms and principles on the other. Every economic system create a framework in which a socio-economic communities can take advantage of the natural resources and human for the sake of production and distribute them for consumption. In this case, Syed NawabHaider Naqvi transform the ethical values of Islam into a set of axioms, that is tauhid (Unity), equilibrium, free will, and responsibility. A set of axioms can be used as a reference in formulating economic behavior consistent. Axiomatic approach in Islamic economics is an analytical tool used to draw up the basic elements of Islamic economics. With sourced from the Al-Qur’an and the Hadith, the Islamic ethical axiom set has been built to meet the five characteristics logically fundamental axioms of the system.